Rapid rule out of myocardial infarction with the use of copeptin as a biomarker for cardiac injury. Issue 9 (September 2014) - Jayasinghe, R.; Narasimhan, S.; Tran, T. H.; Paskaranandavadivel, A.
Abstract Copeptin is a non‐specific marker of an endogenous stress response. A dual biomarker marker approach involving the simultaneous use of troponin and copeptin assays may assist early exclusion of acute coronary syndrome in Australian emergency departments. The utility and limitations of this approach are discussed.